2018
DOI: 10.1038/s41388-017-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Employing mesenchymal stem cells to support tumor-targeted delivery of extracellular vesicle (EV)-encapsulated microRNA-379

Abstract: Adult Mesenchymal Stem Cells (MSCs) have a well-established tumor-homing capacity, highlighting potential as tumor-targeted delivery vehicles. MSCs secrete extracellular vesicle (EV)-encapsulated microRNAs, which play a role in intercellular communication. The aim of this study was to characterize a potential tumor suppressor microRNA, miR-379, and engineer MSCs to secrete EVs enriched with miR-379 for in vivo therapy of breast cancer. miR-379 expression was significantly reduced in lymph node metastases compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(102 citation statements)
references
References 52 publications
2
95
0
Order By: Relevance
“…Similar results were shown in a breast cancer study (O'Brien et al, 2018) employing ADSC-EVs enriched with miR-379, a tumor suppressor miRNA whose expression is down-regulated in breast cancer (Khan et al, 2013). It was found that the miR-379-enriched ADSC-EVs significantly inhibited tumor growth without adverse effects in mice over the 6 weeks of monitoring (O'Brien et al, 2018). These findings suggested a potential application of genetically engineered ADSCs to promote secretion of EVs encapsulated in tumor suppressor miRNAs may be a promising, novel strategy to treat cancer.…”
Section: Adsc-derived Extracellular Vesicles In Cancersupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were shown in a breast cancer study (O'Brien et al, 2018) employing ADSC-EVs enriched with miR-379, a tumor suppressor miRNA whose expression is down-regulated in breast cancer (Khan et al, 2013). It was found that the miR-379-enriched ADSC-EVs significantly inhibited tumor growth without adverse effects in mice over the 6 weeks of monitoring (O'Brien et al, 2018). These findings suggested a potential application of genetically engineered ADSCs to promote secretion of EVs encapsulated in tumor suppressor miRNAs may be a promising, novel strategy to treat cancer.…”
Section: Adsc-derived Extracellular Vesicles In Cancersupporting
confidence: 91%
“…Lou et al demonstrated that miR-122 transfected ADSC-secreted EVs were rich in miR-122, and that uptake of these EVs by cultured HCC cells lead to increased chemosensitivity to chemotherapeutic agents and significant reduction in tumor growth in vivo (Lou et al, 2015). Similar results were shown in a breast cancer study (O'Brien et al, 2018) employing ADSC-EVs enriched with miR-379, a tumor suppressor miRNA whose expression is down-regulated in breast cancer (Khan et al, 2013). It was found that the miR-379-enriched ADSC-EVs significantly inhibited tumor growth without adverse effects in mice over the 6 weeks of monitoring (O'Brien et al, 2018).…”
Section: Adsc-derived Extracellular Vesicles In Cancermentioning
confidence: 57%
“…Therefore, we do not think that exosomal miRNAs could be associated with therapeutic effect by the modulation of target gene expression in tumor cells. This does not exclude the possibility of the active involvement of exosomal miRNAs in the gene regulation in recipient tumor cells . A number of studies in the field of regenerative medicine have shown that nanoparticles produced by MSCs exert their therapeutic effects in several diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements developed recently are focused on the treatment of single or various cancers. The systemic administration of such EVs has demonstrated therapeutic effects in cancer and its metastases [69]. Consider now three other examples specific for single cancers.…”
Section: Diagnosis and Therapymentioning
confidence: 99%
“…Another approach, already promising for in-vivo therapy of breast cancer, is based on the engineering of MSC cells competent for the release of EVs enriched in the microRNA, miR-379. The systemic administration of such EVs has demonstrated therapeutic effects in cancer and its metastases [69].…”
Section: Diagnosis and Therapymentioning
confidence: 99%